Welfare reform and beyond : the future of the safety net - Sawhill, Isabel V. (Brookings Institution, 2002)
The Brookings Institution's Welfare Reform & Beyond Initiative was created to inform the critical policy debates surrounding the upcoming congressional reauthorization of the Temporary Assistance for Needy Families (TANF) program and a number of related programs that were created or dramatically altered by the 1996 landmark welfare reform legislation. The goal of the project has been to take the large volume of existing and forthcoming research studies and shape them into a more coherent and policy-oriented whole. This capstone collection gathers twenty brief essays (published between January 2001 and February 2002) that focus on assessing the record of welfare reform, specific issues likely to be debated before the TANF reauthorization, and a broader set of policy options for low-income families. It is a reader-friendly volume that will provide policymakers, the press, and the interested public with a comprehensive guide to the numerous issues that must be addressed as Congress considers the future of the nation's antipoverty policies. The collection covers the following topics and features a new introduction from the editors: - An Overview of Effects to Date - Welfare Reform Reauthorization: An Overview of Problems and Issues - A Tax Proposal for Working Families with Children - Welfare Reform and Poverty - Reducing Non-Marital Births - Which Welfare Reforms are Best for Children' - Welfare and the Economy - What Can Be Done to Reduce Teen Pregnancy and Out-of-Wedlock Births' - Changing Welfare Offices - State Programs - Welfare Reform and Employment - Fragile Families, Welfare Reform, and Marriage - Health Insurance, Welfare, and Work - Helping the Hard-to-Employ - Sanctions and Welfare Reform - Child Care and Welfare Reform - Job Retention and Advancement in Welfare Reform - Housing and Welfare Reform - Non-Citizens - Block Grant Structure - Food Stamps - Work Support System - Possible Welfare Reform in the Cities.
Keywords: Temporary Assistance for Needy Families (Program); Temporary Assistance for Needy Families (Programme); Public welfare -- United States.; Welfare recipients -- Employment -- United States.; Aid to families with dependent children programs -- Law and legislation -- United States.; Public welfare administration -- Law and legislation -- United States.; Aide sociale -- États-Unis.; Aide sociale -- Bénéficiaires -- Travail -- États-Unis.; Aide sociale aux familles avec enfants à charge -- Droit -- États-Unis.; Aide sociale -- Administration -- Droit -- États-Unis.; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; SOCIAL SCIENCE -- Human Services.; Aid to families with dependent children programs -- Law and legislation; Public welfare; Public welfare administration -- Law and legislation; Welfare recipients -- Employment; United States; Sozialhilfe; Reform; Aufsatzsammlung; Prognose; USA